Putting the brakes on the "drive to eat": Pilot effects of naltrexone and reward-based eating on food cravings among obese women. (December 2015) - Mason, Ashley E.; Laraia, Barbara; Daubenmier, Jennifer; Hecht, Frederick M.; Lustig, Robert H.; Puterman, Eli; Adler, Nancy; Dallman, Mary; Kiernan, Michaela; Gearhardt, Ashley N.; Epel, Elissa S.
Abstract: Purpose: Obese individuals vary in their experience of food cravings and tendency to engage in reward-driven eating, both of which can be modulated by the neural reward system rather than physiological hunger. We examined two predictions in a sample of obese women: (1) whether opioidergic blockade reduced food-craving intensity, and (2) whether opioidergic blockade reduced an association between food-craving intensity and reward-driven eating, which is a trait-like index of three factors (lack of control over eating, lack of satiation, preoccupation with food). Methods: Forty-four obese, pre-menopausal women completed the Reward-Based Eating Drive (RED) scale at study start and daily food-craving intensity on 5 days on which they ingested either a pill-placebo (2 days), a 25 mg naltrexone dose (1 day), or a standard 50 mg naltrexone dose (2 days). Results: Craving intensity was similar under naltrexone and placebo doses. The association between food-craving intensity and reward-driven eating significantly differed between placebo and 50 mg naltrexone doses. Reward-driven eating and craving intensity were significantly positively associated under both placebo doses. As predicted, opioidergic blockade (for both doses 25 mg and 50 mg naltrexone) reduced the positive association between reward-driven eating and craving intensity to non-significance. Conclusions: Opioidergic blockade did not reduce craving intensity; however, blockade reduced an association between trait-like reward-driven eating and daily food-craving intensity, and may help identify an important endophenotype within obesity. Highlights: Opioidergic blockade does not uniformly reduce food-craving intensity. Reward-Based Eating Drive (RED) correlates with daily food-craving intensity. Opioidergic blockade reduces an association between RED and food-craving intensity. Together, opioidergic blockade and RED may identify an obesity endophenotype.